Effects of ultrasound-guided external oblique intercostal plane block on the postoperative analgesia after open liver surgery: study protocol for a randomised controlled trial - Jiali Tang; Qingqing Hua; Yuelun Zhang; Weihua Nie; Songlin Yu; Jinlan Zhang (Trials)
Abstract Background Open liver surgery remains a primary surgical approach for complex liver resections and liver transplantation. However, the postoperative pain management is still a major challenge. Ultrasound-guided external oblique intercostal (EOI) plane block is a novel approach of regional anaesthesia and has a great potential to relieve postoperative pain after upper abdominal surgeries. This study aims to investigate the efficacy and safety of ultrasound-guided EOI plane block in managing postoperative pain after open liver surgery. Methods Seventy-four participants scheduled for open liver surgery will be randomly assigned to either the intervention group, receiving an ultrasound-guided EOI plane block with a single dose of 30 ml 0.375% ropivacaine, or the control group, which will not receive this block. All participants will be provided with opioid-based patient-controlled intravenous analgesia (PCIA) postoperatively. The primary outcome is resting pain score at 3 h postoperatively, assessed using numerical rating scale. Secondary outcomes include pain score at 6, 24, 48, and 72 h postoperatively, perioperative opioid consumption, remedial analgesics within 72 h postoperatively, PCIA usage within postoperative 72 h, postoperative recovery, length of hospital stay, postoperative side effects, block-related complications, and ropivacaine plasma concentration of participants receiving the block. Discussion This study is a randomised controlled trial to evaluate the efficacy and safety of ultrasound-guided EOI plane block for postoperative analgesia after open liver surgery. As regional anaesthesia plays an important role in the multimodal pain management, EOI plane block may prove to be an effective regional technique for enhancing postoperative pain relief and contributing to enhanced recovery after open liver surgery. Trial registration Chinese Clinical Trial Registry ChiCTR2200065745. Registered on November 14, 2022.